Effect of Ranirestat, a New Aldose Reductase Inhibitor, on Diabetic Retinopathy in SDT Rats. (25th August 2014) - Toyoda, Fumihiko; Tanaka, Yoshiaki; Ota, Ayumi; Shimmura, Machiko; Kinoshita, Nozomi; Takano, Hiroko; Matsumoto, Takafumi; Tsuji, Junichi; Kakehashi, Akihiro
Abstract : Purpose . To evaluate the effect of ranirestat, a new aldose reductase inhibitor (ARI), on diabetic retinopathy (DR) in Spontaneously Diabetic Torii (SDT) rats. Methods . The animals were divided into six groups, normal Sprague-Dawley rats ( n = 8 ), untreated SDT rats ( n = 9 ), ranirestat-treated SDT rats (0.1, 1.0, and 10 mg/kg/day, n = 7,   8, and   6, resp.), and epalrestat-treated SDT rats (100 mg/kg/day, n = 7 ) . Treated rats received oral ranirestat or epalrestat once daily for 40 weeks after the onset of diabetes. After the eyes were enucleated, the retinal thickness and the area of stained glial fibrillary acidic protein (GFAP) were measured. Results . The retinas in the untreated group were significantly thicker than those in the normal and ranirestat-treated (0.1, 1.0, and 10 mg/kg/day) groups. The immunostained area of GFAP in the untreated group was significantly larger than that in the normal and ranirestat-treated (1.0 and 10 mg/kg/day) groups. There were no significant differences between the untreated group and epalrestat-treated group in the retinal thickness and the area of stained GFAP. Conclusion . Ranirestat reduced the retinal thickness and the area of stained GFAP in SDT rats and might suppress DR and have a neuroprotective effect on diabetic retinas.